The mass of the exo-Venus Gliese 12 b, as revealed by HARPS-N, ESPRESSO, and CARMENES - Turner, Daisy; Eschen, Yoshi Nike Emilia; Murgas, Felipe; Mortier, Annelies; Wilson, Thomas G; Fernández Fernández, Jorge; Gromek, Nicole; Morello, Giuseppe; Tabernero, Hugo M; Egger, Jo Ann; Vissapragada, Shreyas; Caballero, José A; et al. (Monthly notices of the Royal Astronomical Society, 2026)
Small temperate planets are prime targets for exoplanet studies due to their possible similarities with the rocky planets in the Solar system. M dwarfs are promising hosts since the planetary signals are within our current detection capabilities. Gliese 12 b is a Venus-sized temperate planet orbiting a quiet M dwarf. We present here the first precise mass measurement of this small exoplanet. We performed a detailed analysis using HARPS-N (High Accuracy Radial velocity Planet Searcher for the Northern Hemisphere), ESPRESSO (Echelle Spectrograph for Rocky Exoplanets and Stable Spectroscopic Observations), and CARMENES (Calar Alto high-Resolution search for M dwarfs with Exoearths with Near-infrared and optical Echelle Spectrographs) radial velocities, along with new and archival TESS (Transiting Exoplanet Survey Satellite), CHEOPS (CHaracterising ExOPlanet Satellite), and MuSCAT2/3 (Multicolor Simultaneous Camera for studying Atmospheres of Transiting exoplanets) photometry data. From fitting the available data, we find that the planet has a radius of $R_p = 0.93± 0.06 \, \mathrm{R_{\rm{\oplus }}}$ and a mass of $M_p = 0.95^{+0.29}_{-0.30} \, \mathrm{M_{\rm{\oplus }}}$ (a $3.2σ$ measurement of the semi-amplitude $K=0.67± 0.21\, \mathrm{m\, s^{-1}}$), and is on an orbit with a period of $12.761418^{+0.000060}_{-0.000055}\, d$. A variety of techniques were utilized to attenuate stellar activity signals. Gliese 12 b has an equilibrium temperature of $T_eq=317 ± 8\, K$, assuming an albedo of zero, and a density consistent with that of Earth and Venus ($ρ _p=6.4± 2.4\, \mathrm{g\, cm^{-3}}$). We find that Gliese 12 b has a predominantly rocky interior and simulations indicate that it is unlikely to have retained any of its primordial gaseous envelope. The bulk properties of Gliese 12 b place it in an extremely sparsely populated region of both mass-radius and density-$T_eq$ parameter space, making it a prime target for follow-up observations, including Lyman-$α$ studies.
Vorab veröffentlicht: 07. Oktober 2025
Gesehen am 20.02.2026